THE PRACTICE OF PLACING SOVEREIGN INTERNATIONAL BONDS OF THE REPUBLIC OF UZBEKISTAN IN NATIONAL CURRENCY ON INTERNATIONAL FINANCIAL MARKETS - Madaminova, Nargiza Ibadullaevna; Gaybullayeva , Dilafruz (Educational Research in Universal Sciences, 2023)
The article analyzes the effective use of funds from the placement of international bonds of the Republic of Uzbekistan, including the analysis of sovereign bonds, the correct assessment of their profitability, and provides relevant conclusions.